1998
DOI: 10.1159/000029041
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia, Alexithymia and Locus of Control in Unipolar Major Depressive Disorders

Abstract: The relationship between anhedonia, alexithymia and locus of control was studied in a group of healthy subjects (n = 56) and in a group of unipolar major depressives (n = 59). These dimensions were rated using the Physical Anhedonia Scale (PAS), the Toronto Alexithymia Scale (TAS) and the Internal Powerful others and Chance Scale. The unipolar major depressives were divided into two subgroups using the endogenomorphic subscale of the Hamilton Depression Rating Scale. There are respectively 25 and 17 depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
3
17
1
4
Order By: Relevance
“…These results confirm an association between alexithymia and some sexual disorders. This association is unspecific as in some other psychiatric disorders [19,20]. The current study is the first report on TAS factor scores in outpatients with sexual disorders.…”
Section: Discussionmentioning
confidence: 68%
“…These results confirm an association between alexithymia and some sexual disorders. This association is unspecific as in some other psychiatric disorders [19,20]. The current study is the first report on TAS factor scores in outpatients with sexual disorders.…”
Section: Discussionmentioning
confidence: 68%
“…Among college students, individuals with higher levels of depression (as measured by the Beck Depression Inventory) tended to report paying less attention to their emotions, though the association was very weak ). In contrast, Loas et al (1998) found that individuals with MDD did not differ significantly from non-psychiatric controls in externally-oriented thinking (which past research has found is strongly negatively correlated with attention to emotion; e.g., Coffey et al 2003).…”
Section: Introductionmentioning
confidence: 69%
“…Η μεγάλη πλειοψηφία των ερευνών καταφάσκει τη θετική σχέση μεταξύ κατάθλιψης και αλεξιθυμίας (Loas et al, 1998, Berthoz et al, 1999, Marchesi et al, 2000, Honkalampi et al, 2000a, Honkalampi et al, 2000b, Honkalampi et al, 2001b, Bankier et al, 2001, Hintikka et al, 2001, Saarijarvi et al, 2001, Honkalampi et al, 2004, Gulec et al, 2005, Nakao et al, 2005 συν., μετά από 12μηνη παρακολούθηση σε ένα δείγμα 1584 Φιλανδών, προτείνουν ότι τα αλεξιθυμικά χαρακτηριστικά είναι στενά συνδεδεμένα με τα καταθλιπτικά συμπτώματα (Honkalampi et al, 2001c). Οι Gunzelmann και συν.…”
Section: σχέση αλεξιθυμίας-κατάθλιψηςunclassified
“…Έτσι, οι Loas και συν. διαπίστωσαν υψηλότερα σκορ στις κλίμακες της κατάθλιψης και της αλεξιθυμίας στους καταθλιπτικούς ασθενείς, σε σχέση με τους μάρτυρες (Loas et al, 1998). Στα ίδια αποτελέσματα κατέληξαν και οι Marchesi και συν., δουλεύοντας ανεξάρτητα από τους πρώτους (Marchesi et al, 2000).…”
Section: σχέση τιμών επιθετικότητας και αλεξιθυμίαςunclassified
See 1 more Smart Citation